IN SILICO, DEVELOPMENT AND CHARACTERIZATION OF CILNIDIPINE ANALOGUES FOR ENHANCED SOLUBILITY AND THERAPEUTIC POTENTIAL IN THE TREATMENT OF ANGINA PECTORIS - KROSURI, PAVANKUMAR; MOHAN, MOTHILAL (International Journal of Applied Pharmaceutics, 2025)
Objective: Angina pectoris remains a significant clinical challenge due to the limitations of current therapies, such as inadequate efficacy and undesirable side effects. This study aims to address these issues by developing a novel treatment approach based on Cilnidipine analogues and nanotechnology, focusing on the lead compound Cilnidipine Analogue (CC5; ZINC101069658). Methods: CC5 was identified as the most promising candidate due to its optimal balance of lipophilicity, solubility, absorption, and synthetic feasibility. A bioinformatics-driven approach uncovered 60 potential target hub genes related to angina pectoris, with Protein-Protein Interaction (PPI) analysis highlighting Estimated Glomerular Filtration Rate (EGFR) as a key target. Molecular docking and Molecular Dynamics simulations confirmed the stability and strong binding affinity of CC5 with the EGFR-associated protein (5wb7). SWISSADME analysis revealed moderate lipophilicity, poor water solubility, and low gastrointestinal absorption, while HOMO-LUMO studies suggested enhanced chemical stability. The Taguchi design of experiments indicated that stirring speed was critical for nanoparticle size, and stabilizer concentration significantly impacted Encapsulation Efficiency (EE) and zeta potential. Results: Molecular docking studies showed a strong binding affinity of-8.6 kcal/mol with EGFR, while pharmacokinetic evaluations indicated favourable absorption and moderate lipophilicity, supporting CC5’s potential as an optimized therapeutic agent for angina pectoris. CC5 nanoparticles exhibited a 2.63-fold increase in solubility compared to the parent compound. Fourier Transform Infrared Spectroscopy, Transmission Electron Microscopy, and X-ray Diffraction characterization confirmed the successful nanoparticle formulation. In vitro dissolution studies demonstrated superior drug release from CC5-loaded nanoparticulate oral disintegrating tablets, with the CAF9 (CC5 Formulation 9) showing rapid onset of action and a significantly improved release profile (98.89±1.10% at 30 min) compared to controlled (80.58%) and marketed preparations (18.85%). Conclusion: The study demonstrates the therapeutic potential of ZINC101069658, a CC5, through its enhanced solubility and reduced Crystallinity. The lead compound was made into Nanoparticles using Pluronic F 188 as carrier. These nanoparticles were further formulated to oral disintegrating tablets for rapid drug release good stability compared to conventional tablets. These findings suggest that ZINC101069658 could be a promising candidate for the treatment of angina pectoris.